2015
DOI: 10.1021/acssuschemeng.5b00544
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Capture of the Greenhouse Gas CO2 in Polymers

Abstract: Owing to their high physicochemical stability and low skeleton density, polymers are highly promising for capturing the greenhouse gas CO 2 . However, complicated monomers, expensive catalysts, and/or severe conditions are usually required for their synthesis, which makes the process costly, tedious, and hard to scale up. In this paper, a facile nucleophilic substitution reaction is developed to synthesize polymers from low-cost monomers, namely chloromethylbenzene and various diamines. Due to the appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(108 citation statements)
references
References 72 publications
3
104
1
Order By: Relevance
“…Nitrogen, oxygen, sulphur and phosphorus atoms are always incorporated into POPs to increase selectivity and capture capacity of CO 2 . 33,58,[60][61][62][63][64][65][66][67][68][69][70] This part will be detailed discussed in the following. By replacing the phenyl group with different functional pyridyl or thiophenyl groups is the most commonly used method to incorporating heteroatomic into skeleton of POPs.…”
Section: Heteroatomic Skeletonmentioning
confidence: 99%
“…Nitrogen, oxygen, sulphur and phosphorus atoms are always incorporated into POPs to increase selectivity and capture capacity of CO 2 . 33,58,[60][61][62][63][64][65][66][67][68][69][70] This part will be detailed discussed in the following. By replacing the phenyl group with different functional pyridyl or thiophenyl groups is the most commonly used method to incorporating heteroatomic into skeleton of POPs.…”
Section: Heteroatomic Skeletonmentioning
confidence: 99%
“…Both chemical and physical adsorption techniques have been employed in practical applications . For example, the traditional method for fixing CO 2 is to bubble the mixed gases through aqueous alkanolamine . Although chemical adsorption shows good performance with regard to capacity and selectivity, its poor portability as well as high regeneration and maintenance costs limit its application.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] For example, the traditional methodf or fixing CO 2 is to bubble the mixed gases through aqueous alkanolamine. [6] Although chemicala dsorption shows good performance with regard to capacitya nd selectivity,i ts poor portability as well as high regeneration and maintenance costs limit its application.A mong physicala dsorption materials, microporous organic polymers (MOPs) possesst he flexibility for material design to obtain inherentl ightweight, desirable structures,p roperties, and functions, in comparison with their inorganic counterparts [zeolites [7,8] and metal-organic frameworks (MOFs) [9,10] ]. For the past decades, the design andp reparation of MOPs with new buildingb locks has attracted significant attention in both aca-demic and industrial research to circumvent the problems of high cost and low stability usually found in MOPs, including covalent organic frameworks (COFs), [11,12] polymers of intrinsic microporosity (PIMs), [13,14] and conjugated microporous polymers (CMPs).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on the separationo fC O 2 concerned new adsorbents such as metal-organic frameworks (MOFs), [29][30][31][32][33][34] N-doped porous carbons (NPCs), [35] microporous coordination polymers (MCPs), [36] covalento rganic polymers (COPs), [37][38][39] and porous organic polymers (POPs) [40][41][42] compared to commercial adsorbents (i.e., molecular sieves,a ctivated carbons,a nd silica gel) [43][44][45][46] and relied on theoretical selectivity analysis.E ven with the wide range of utilization in this field, there is still al ack of information on the characteristic behavior of CO 2 adsorption in multicomponent mixtures.T here are no detailed studies for comparison between these types of commercial adsorbents, which are still pioneering materials for CO 2 removal, [47][48][49] related to their partialc omponent uptake performances for awide range of mixturec ombinations and conditions. Molecular sieve zeolite (MSZ) adsorbents are one of the most popular solid adsorbents utilizedn ormally for the separation and purification of multicomponent mixtures.T hese adsorbents have low Si/Al ratios (e.g.,1 3X and 5A zeolite), which results in higher uptake amounts of CO 2 at low pressures ( % 2.5 mmol g À1 at 298 Ka nd 0.1 bar).…”
Section: Introductionmentioning
confidence: 99%